Exploring the roles of paradoxical tensions, paradoxical thinking, and team psychological capital on the creativity of engineering university students - Huifen Guo; Zhen Zhou; Fengqi Ma (BMC Psychology)
Abstract Background The multifaceted challenges encountered by engineering university students generate paradoxical tensions, which serve as catalysts for fostering creativity. Engaging in paradoxical thinking during academic pursuits enhances students’ ability to solve complex engineering problems. Despite this, the intricate interconnections among paradoxical tensions, paradoxical thinking, and the creativity of engineering university students remain ambiguous. Methods This study aimed to explore the gap by surveying 1,410 engineering students in China, examining how paradoxical thinking mediates the relationship between paradoxical tensions and creativity. Additionally, it investigated the moderating impact of team psychological capital on the associations between paradoxical tensions and both paradoxical thinking and creativity. SPSS 24.0 was initially used to convert the cleaned data into a “.csv” format, and Smart PLS (v.4.0.9.5) was then employed to assess the model. Results The findings reveal a positive influence of paradoxical tensions on creativity and thinking. Notably, paradoxical thinking emerges as a significant contributor to enhancing the creativity of engineering university students. Furthermore, the findings show that paradoxical tensions enhance creativity by influencing paradoxical thinking. While team psychological capital emerged as a significant factor in moderating the link between paradoxical tension and creativity, its role in moderating the association between paradoxical tension and paradoxical thinking was not statistically significant. Conclusions This study revealed how paradoxical tensions among engineering university students influence creativity through paradoxical thinking moderated by team psychological capital. The findings provide new insights for researchers to understand paradoxical tensions, paradoxical thinking, team psychological capital, and the underlying psychological mechanism for engineering university students’ creativity better, and they have practical implications for education administrators.